Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Mitra Dana Top Finance Cabang Bandung - Prayogi, Muhammad Sandi; Atmawinata, Maya R (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the effect of work motivation and discipline on employee performance at PT. Mitra Dana Top Finance Branch Bandung. The method used is descriptive and quality with a quantitative approach. The population in this study were all employees of PT. Mitra Dana Top Finance Branch Bandung, while the sampling technique used the Non-Probability Sampling technique or saturated samples, amounting 40 respondents. The data collection methods used questionnaires, observation and literature studies, while data analysis methods used quality tests, classical assumption tests, and hypothesis testing using the Programs Statistics SPSS 26. The results of this study motivation have a positive and significant effect on employee performance with a tcount of 2.721 > ttable of 2.026 and sig. 0.010 < a 0.05, and work discipline also has a positive and significant effect on employee performance with a tcount of 2.707 > ttable of 2.026 and sig. 0.010 < a 0.05. The R2 value in this study was obtained at 45.2% which indicates that work motivation and discipline affect employee performance, while the remaining 54.8% is influenced by other factors that were not examined in this study. Keywords: Motivation, Work Discipline and Employee Performance.